Pemikiran Hukum dan Fatwa Abdullah ibn Mas’ud - Busyro, Busyro (Alhurriyah, 2009)
As one of Prophet Muhammad companion who often together with him, Ibn Mas?ud was believed to be a hakim (judge) and mufti (adviser on religious law for a region) in the era of Umar bin Khatab leadership. In some cases, his method in some ideas much influenced by the tradition and scientific given by Umar bin Khatab at that time. Related with his role as a hakim and mufti, he has produced a lot of decisional law and guidance (fatwa) that sometimes it was very difficult to be decided even it was very different with the prophet statements (hadis). He has forceful basic ideas which are regarded as a good respond related with social problem occurred in the period. From some examples of his guidance related to the social problem, it showed that there was a relationship between his guidance and the condition among the society at that time. Finally, we could see that the last decision of his guidance was aimed to realize the purpose of deciding the Islamic law itself; realizing the goodness or benefits for the society and rejecting such kind of things that could appear any depravation.